Angiopoietin‐like protein 4 deficiency augments liver fibrosis in liver diseases such as nonalcoholic steatohepatitis in mice through enhanced free cholesterol accumulation in hepatic stellate cells. Issue 5 (7th April 2021) - Teratani, Toshiaki; Tomita, Kengo; Wada, Akinori; Sugihara, Nao; Higashiyama, Masaaki; Inaba, Kenichi; Horiuchi, Kazuki; Hanawa, Yoshinori; Nishii, Shin; Mizoguchi, Akinori; Tanemoto, Rina; Ito, Suguru; et al.
Abstract: Aim: We recently reported that lipoprotein lipase (LPL)‐mediated free cholesterol (FC) accumulation in hepatic stellate cells (HSCs) augmented liver fibrosis in non‐alcoholic steatohepatitis (NASH). The aim of the present study was to explore the role of angiopoietin‐like protein 4 (Angptl4), an LPL inhibitor, in the pathogenesis of liver fibrosis in NASH. Methods: Angptl4‐deficient or wild‐type mice were used to investigate the role of Angptl4 in the pathogenesis of NASH induced by feeding a methionine‐ and choline‐deficient diet. We also examined the effect of Angptl4 on FC accumulation in HSCs, and the subsequent activation of HSCs, using Angptl4‐deficient HSCs. Results: In the NASH model, Angptl4‐deficient mice had significantly aggravated liver fibrosis and activated HSCs without enhancement of hepatocellular injury, liver inflammation, or liver angiogenesis. FC levels were significantly higher in HSCs from Angptl4‐deficient mice than in those from wild‐type mice. Treatment with Angptl4 reversed low‐density lipoprotein‐induced FC accumulation in HSCs through the inhibition of LPL. The Angptl4 deficiency‐induced FC accumulation in HSCs suppressed HSC expression of the transforming growth factor‐ β (TGF‐ ß ) pseudoreceptor, bone morphogenetic protein, and activin membrane‐bound inhibitor, and sensitized HSCs to TGF‐ β ‐induced activation in vivo and in vitro. Conclusions: Angptl4 plays an important role in the pathogenesis of FC accumulation in HSCs. In addition, regulation of FC levels in HSCs by Angptl4 plays a critical role in the pathogenesis of liver fibrosis in NASH. Thus, Angptl4 could represent a novel therapeutic option for NASH.